2004
DOI: 10.1002/pros.20014
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor protein expression in prostatic tissues in black and caucasian men

Abstract: Variations in AR expression between subpopulations may contribute to the phenotypic differences of prostatic diseases in Black and Caucasian men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…AR expression in prostate cancer has been previously reported to be increased in black Americans in comparison with Caucasian patients, supporting the hypothesis that differential expression of AR protein may be driven at least in part by genetic events (22). Moreover, short variants of the AR gene have been shown to induce increased transcriptional activity and high AR protein levels (23).…”
Section: Discussionmentioning
confidence: 56%
“…AR expression in prostate cancer has been previously reported to be increased in black Americans in comparison with Caucasian patients, supporting the hypothesis that differential expression of AR protein may be driven at least in part by genetic events (22). Moreover, short variants of the AR gene have been shown to induce increased transcriptional activity and high AR protein levels (23).…”
Section: Discussionmentioning
confidence: 56%
“…Studies comparing the distribution of allele sizes for the CAG and GGN microsatellite repeat polymorphisms between different populations have noted shorter repeat lengths, on average, in men of African versus Caucasian descent (Kittles et al 2001;Esteban et al 2006). Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004). Specifically, AR protein expression levels were estimated to be 22% higher in benign prostate cancer tissues and 81% higher in malignant prostate cancer tissues in African Americans versus Caucasian Americans (Gaston et al 2003).…”
Section: Introductionmentioning
confidence: 61%
“…17 Moreover, recent evidence has indicated a higher androgen receptor expression in BPH epithelium of African-American compared to Caucasian men. 18 While we acknowledge the controversial reported correlation between testosterone levels and sexual health in eugonadal men, it is clear that testosterone levels and mainly the bioavailability of testosterone have a significant impact on sexual behavior and ejaculatory function in hypogonadal men. 19 In our subanalysis, total testosterone and hypogonadism did not seem to have a significant impact when sexual performance was compared in both groups after adjusting for all other risk factors mainly for comorbidities and age.…”
Section: Correlation Between Luts and Edmentioning
confidence: 79%